Efektivitas Pupuk Organik Cair Jerami Padi dan Kotoran Sapi terhadap Pertumbuhan Tanaman Sawi (Brasicca juncea L.) - Anisa Rizki Nastiti; Aminah Asngad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The mustard plant (Brassica juncea L.) is loved by everyone because it has lots of nutrients and is also good for health. This research aims to determine the effectiveness of liquid organic fertilizer from rice straw and cow dung on the growth of mustard greens. The method used in this research was an experimental method with a Completely Randomized Design (CRD) with 2 factors, namely the dose of liquid organic fertilizer (P₁ = 10 ml and P₂ = 13 ml) and the time of application of liquid organic fertilizer (W₁ = once every 5 days and W₂ = once every 7 days). The results of research on liquid organic fertilizer from rice straw and cow dung can effectively accelerate growth in height, number of leaves and wet weight in mustard greens (Brassica juncea L.). The growth of mustard greens was very good in the P₂W₁ treatment (13 ml dose every 5 days) which produced mustard plants with an average height of 35.1 cm, an average number of leaves of 17.3, and an average fresh weight of mustard greens. average 165.3 grams.